2002
DOI: 10.1096/fj.02-0115fje
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor transactivation mediates the tonic and fibrogenic effects of endothelin in the aortic wall of transgenic mice

Abstract: Vascular remodeling and rearrangement of the extracellular matrix formation are among the major adaptive mechanisms in response to a chronic blood pressure increase. Vasoactive peptides, such as endothelin, participate in hypertension-associated vascular fibrosis by stimulating collagen I formation and increasing contractility of arterial wall. In the present study, we tested the hypothesis that activation of the epidermal growth factor (EGF) receptor pathway mediates these events. Experiments were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 37 publications
4
77
1
3
Order By: Relevance
“…For example, angiotension II and endothelin induce EGFR activation and renal fibrogenesis in the kidney, and mice overexpressing a dominant negative isoform of EGFR or subjected to EGFR inhibitors have reduced fibrotic lesions. 12,37 These data suggest that EGFR not only transduces profibrotic signals from its ligands but also from some non-EGFR ligands. With this property, many metabolic, hormonal, and hemodynamic factors may induce renal fibrosis through activation of EGFR.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, angiotension II and endothelin induce EGFR activation and renal fibrogenesis in the kidney, and mice overexpressing a dominant negative isoform of EGFR or subjected to EGFR inhibitors have reduced fibrotic lesions. 12,37 These data suggest that EGFR not only transduces profibrotic signals from its ligands but also from some non-EGFR ligands. With this property, many metabolic, hormonal, and hemodynamic factors may induce renal fibrosis through activation of EGFR.…”
Section: Discussionmentioning
confidence: 92%
“…36 EGFR activation is involved in endothelininduced renal vascular and glomerular fibrosis. 37 Furthermore, interstitial fibrosis and tubular atrophy from prolonged ischemia and chronic infusion of angiotensin II were associated with increased EGFR activity. 12,21 However, the underlying mechanism by which EGFR activation contributes to renal fibrosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Use of an EGF receptor-tyrosine kinase inhibitor in a preventive way, normalized the MAPK activation, inhibited the abnormal increase of collagen I gene expression, decreased proteinuria and creatininemia and prevented the development of renal vascular and glomerular fibrosis. 6,33 From these studies, it appears that blockade or antagonism of growth factor receptors offer an interesting choice as therapy against fibrosis. However, the experience from human trials with long-term blockade of growth factor action indicates several undesired secondary effects.…”
Section: Mediators Of the Angiotensin II Actionmentioning
confidence: 99%
“…The phosphorylation of EGF receptor leads to the activation of the MAPK 42/44 pathway and the formation of the AP-1 transcriptional complex. [3][4][5][6] Antagonists of endothelin or EGF receptors or inhibitors of MAPK phosphorylation cancelled the angiotensin II-induced activation of collagen I gene. Another way of angiotensin action on collagen I gene is mediated by the activation of the transforming growth factor b (TGFb)/Smad pathway.…”
mentioning
confidence: 99%
“…Endothelin-1 acts acutely via the EGFR to promote vasoconstriction both in isolated aortic rings and in vivo, whereas over time the same pathway can stimulate collagen transcription leading to vascular fibrosis. 40 Ang II stimulation of VSMC hypertrophy is undoubtedly the most extensively characterized vascular outcome of EGFR transactivation. Numerous studies by Eguchi et al, 41 among others, have shown that Ang II stimulates hypertrophy and migration via metalloprotease-dependent shedding of HB-EGF and subsequent EGFR activation.…”
Section: Transactivation Of Egf Receptors: a Common Pathway For Gpcr-mentioning
confidence: 99%